2013
DOI: 10.1590/s2317-17822013000500014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aspects of quality of life in teachers' voice after discharged: longitudinal study

Abstract: DescritoresTo evaluate the long-term effects of voice therapy on the life quality of teachers who were discharged or abandoned the voice therapy for dysphonia. Methods: This was a longitudinal study based on analysis of assessments with teachers of municipal schools in Belo Horizonte, who were referred to voice therapy and were discharged or abandoned the speechlanguage therapy for more than six months. A total of 33 teachers in the discharged group and 20 teachers in the abandoned group were contacted by phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Regarding voice parameters, no changes were found after our Control group's eight-week non-therapy period, which corroborates the findings of Gillivan-Murphy et al 70 This shows that voice clients need straight guidance and feedback from a speech therapist to change their voice behavior in order to change the interaction process of airflow, air pressure, and muscular activity of the vocal cords. 22 Our VAPP results did not change either after the non-therapy period, as also reported by Ferreira et al 71 In contrast to our study, Ribeiro et al 57 reported improvement in their control participants' voice-related quality of life, possibly as a consequence of the so-called Hawthorne effect mentioned above. 69 Teachers with organic laryngeal findings In our initial phoniatric examination organic findings were observed in five teachers: in the Carryover group one polyp in the vocal fold and nodules in one vocal fold; in the Trad group there was one vocal fold hemorrhage, one vocal fold atrophy, and one case of vocal fold nodules.…”
Section: Acoustic Voice Parameters Within the Carryover And Trad Groupssupporting
confidence: 62%
“…Regarding voice parameters, no changes were found after our Control group's eight-week non-therapy period, which corroborates the findings of Gillivan-Murphy et al 70 This shows that voice clients need straight guidance and feedback from a speech therapist to change their voice behavior in order to change the interaction process of airflow, air pressure, and muscular activity of the vocal cords. 22 Our VAPP results did not change either after the non-therapy period, as also reported by Ferreira et al 71 In contrast to our study, Ribeiro et al 57 reported improvement in their control participants' voice-related quality of life, possibly as a consequence of the so-called Hawthorne effect mentioned above. 69 Teachers with organic laryngeal findings In our initial phoniatric examination organic findings were observed in five teachers: in the Carryover group one polyp in the vocal fold and nodules in one vocal fold; in the Trad group there was one vocal fold hemorrhage, one vocal fold atrophy, and one case of vocal fold nodules.…”
Section: Acoustic Voice Parameters Within the Carryover And Trad Groupssupporting
confidence: 62%
“…In Brazil, in 2011, the number of workers away from their labor activities due to illnesses or accidents arising from work activities was 611,576 for temporary absences, and 14,811 for permanent incapacity, causing large consequences on public health with approximate expenses of BRL 63.6 billion According to the results, the perception of health and quality of life of workers on leave from labor activity was significantly worse when compared to the one from the active workers. Several studies have investigated the quality of life for workers in the labor market and in specific occupational groups, such as bank clerks 18 , fire figthers 19 , dentists 20 , motorcycle taxi drivers 21 , public service workers 22 , teachers 23 , and health care professionals 24 , among others. However, in national literature, few investigations analyze the perception of health from workers and the impact of being out of work on the quality of life of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…The Voice Activity and Participation Profile (VAPP) Protocol (11) proposes a self-assessment of the impact of dysphonia in the daily activities of the individual. Studies focusing on voice that use the VAPP as a marker of treatment in the patient's quality of life showed a significant improvement in their fields after speech therapy discharge, indicating the effectiveness of the treatment (4,13,14) . Accordingly, there is a need for studies to verify the association of motivational stages and self-assessment of the impact of dysphonia in the daily activities of the patient during the therapeutic process.…”
Section: Introductionmentioning
confidence: 98%